A novel SIMIDCBC topology driven PMSM for PEV application - Kumar, Chinta Anil; Jothinathan, Kandasamy; Rao, Lingineni Shanmukha (Institute of Advanced Engineering and Science, 2024)
Nowadays, the usage of renewable energy based electric vehicles is increased for reducing CO2 emissions, usage of fossil fuels, energy saving, and transportation cost. As a result, it becomes the most significantly run with combined energy sources and it is good choice which minimizes the energy consumption from charging stations. The available renewable energy is integrated to power-train through power-electronic interface; such interface consists of three-phase inverter with DC-DC boost converter. The combined energy sources like solar-PV/battery are integrated to power-train by employing multi-input non-isolated step-up DC-DC converter for providing continuous power to drive the vehicle. The multi-terminal topologies have efficient, reliable performance, continuous input current, high step-up gain over the conventional DC-DC converters. In this work, a unique framework of combined energy powered switched-inductor based multi-input DC boost converter topology has been proposed to drive the PMSM. The performance of proposed SIMIDCBC topology driven PMSM for PEV application under constant and variable speed conditions are verified by using MATLAB/Simulink tool, simulation results are presented.